The new Platonic interpretation: The contribution of Schleiermacher - Belchior, Mariana Leme (Revista Archai, 2011)
Dating from the 50s, platonic historiography has concentrated on a question of great relevance for the comprehension of Plato’s philosophy, concerning the fact that there is a discrepency between the image which Plato gives his philosophy in the dialogues and the one which his disciples handed down to us. This historiographic problem has already been addressed by Schleiermacher in the XIX century when he elaborated a theory of the dialogue as a form of representation, which links Plato’s philosophy to a direct and indirect communication, capable of influencing several authores through the XIX and XX centuries.